High-entropy alloy with excellent creep property and preparation method thereof
By introducing Laves hard and brittle phase and L12 nano precipitation phase into high-entropy alloys, a soft and hard biphasic structure is formed, and thermal deformation and heat treatment processes are adopted, the shortcomings of tensile strength and plastic properties of high-entropy alloys in engineering applications are solved, and high tensile strength and good plasticity are achieved.
Patent Information
- Application Number
- CN202411796171.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Existing high-entropy alloys are difficult to achieve ultra-high tensile strength while ensuring plastic properties, which limits their widespread use in engineering applications.
By introducing Laves hard and brittle phase and L12 nano precipitation phase into the FCC type HEA matrix, a soft and hard double-phase structure is formed, and the structure structure and performance of the alloy are regulated by combining thermal deformation and heat treatment processes.
It significantly improves the room temperature tensile performance and high temperature creep performance of the material, achieves high tensile strength and good plasticity, and is suitable for engineering applications.
Smart Images

Figure CN119663087A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high entropy alloy materials, and in particular relates to a high entropy alloy with excellent creep performance and a preparation method thereof. Background Art
[0002] High entropy alloy (HEA) is a solid solution formed by 5 or more constituent elements in equiatomic or nearly equiatomic ratios, where the atomic ratio of each principal element is between 5% and 35%. Due to the high thermodynamic entropy effect of mixed configuration, the drastic lattice distortion effect in crystallography, the hysteresis diffusion effect in kinetics and the "cocktail" effect in comprehensive performance, high entropy alloys are superior to traditional alloy materials in physical, chemical and mechanical properties due to their outstanding mechanical properties, good corrosion resistance, excellent thermal stability and outstanding soft magnetic properties, and are considered to be one of the materials with great development potential and the most competitive advantages since the 21st century.
[0003] However, actual engineering applications place higher demands on important performance indicators such as strength and plasticity of structural materials. Single-phase FCC structure HEA systems (such as Cantor alloys) have good plasticity with an elongation of more than 50%, but their tensile strength is only about 500 MPa. The tensile strength of body-centered cubic (BCC) structure HEA systems (such as TiZrHfNb alloys) can reach about 800 MPa, but there is no obvious macroscopic plastic deformation at room temperature. The "inverted" relationship between strength and plasticity seriously restricts the large-scale application of HEA as an advanced structural material in engineering. Therefore, how to maximize the ultra-high tensile strength while ensuring plasticity that can be applied to actual engineering is the focus of current research in the field of high entropy alloys.
[0004] In recent years, eutectic high entropy alloys (EHEAs) have been widely studied and developed rapidly. Compared with the above HEAs, EHEAs have some new structural and performance characteristics such as: (1) close arrangement of multi-phase ultrafine lamellae; (2) near-equilibrium microstructure and strong casting fluidity; (3) adjustable microstructure and high defect structure stability; (4) outstanding creep resistance and fracture strength, which can well achieve the coordinated regulation of strength and plasticity. Taking FeCoCrNiTa-based EHEA as an example, its structure is composed of FCC soft phase and Laves hard phase, among which Laves phase and FCC phase are eutectic reaction products: FCC phase is relatively soft and can provide a large space for dislocation accumulation; Laves hard and brittle, although it provides overall high strength, it is very easy to induce crack initiation and expansion, resulting in the overall brittle fracture of the EHEA. In general, its intrinsic brittleness at room temperature limits the processing deformation ability of the alloy, and the high density cannot meet the demand for low cost. Therefore, it is of great theoretical significance and application value to obtain the composition of new eutectic high-entropy alloys through reasonable composition design methods and to study the microstructure and performance optimization of the alloys. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high entropy alloy with excellent creep performance and a preparation method thereof. By rationally regulating the alloy composition and the subsequent thermal deformation and heat treatment process, the synergistic strengthening effect of the Laves hard-brittle phase and the L12 nano-precipitate phase is introduced into the FCC type HEA matrix to form a positive synergy of the soft-hard dual-phase structure, effectively improving the room temperature tensile properties and high temperature creep properties of the material.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The room temperature tensile properties and high temperature creep properties of the soft-hard dual-phase structure coupling control material of the present invention are expressed as follows: Fe a Co b Cr c Ni d Ta p Al q M n , wherein M is one or more of rare earth elements (Ru and Re), B, C, Si, and P; wherein 10≤a≤20, 20≤b≤25, 10≤c≤20, 25≤d≤35, 5≤p≤10, 0≤q≤8, 0≤n≤5, and a+b+c+d+p+q+n=100.
[0008] As a preferred embodiment, the alloy composition is expressed in terms of atomic mole percentage: Fe a Co b Cr c Ni d Tap Al q M n , wherein M is one or more of rare earth elements, B, C, Si, and P; wherein 16≤a≤20, 23≤b≤25, 16≤c≤20, 25≤d≤28, 5≤p≤8, 5≤q≤8, 0≤n≤1 and a+b+c+d+p+q+n=100, and the rare earth element is Ru and / or Re.
[0009] As a further preferred embodiment, the alloy composition is expressed in terms of atomic mole percentage: Fe a Co b Cr c Ni d Ta p Al q M n , the M is one or more of rare earth elements, B, C, Si, and P; wherein 18≤a≤19, 24.5≤b≤25, 17.5≤c≤18.5, 25.5≤d≤26.5, 5.5≤p≤6.5, 5.5≤q≤6.5, 0.02≤n≤0.1 and a+b+c+d+p+q+n=100, and the rare earth element is Ru and / or Re.
[0010] Among the designed components, Fe 18.95 Co 25 Cr 18 Ni 26 Ta6Al6B 0.05 , Fe 19 Co 25 Cr 18 Ni 26 Ta6Al5Ru 1.5 Among these two solutions, Fe 18.95 Co 25 Cr 18 Ni 26 Ta6Al6B 0.05 The performance of the product obtained by combining this component with the process optimized by the present invention is far superior to other technical solutions of the present invention and existing similar products.
[0011] The present invention discloses a high entropy alloy with excellent creep performance, which contains a soft matrix and a hard phase, wherein the soft matrix includes at least one of an FCC phase and an L12 phase, preferably an FCC phase and an L12 phase, and the hard phase includes at least one of a Laves phase, a B2 phase, a σ phase, and an η phase, preferably a Laves phase.
[0012] Preferably, in the present invention, L12 coherent phase and plastic face-centered cubic (FCC) structure solid solution are the soft matrix.
[0013] In the present invention, the Laves hard phase is a reinforcing phase.
[0014] The Laves phase is preferably a C14 type (MgZn2 structure) Laves phase.
[0015] The soft-hard dual-phase structure of the present invention synergistically controls the strength and plasticity of the material.
[0016] The present invention is the first to provide a high entropy alloy with excellent creep performance and a preparation method thereof. The high entropy alloy has better creep performance than the high-temperature alloy with the Chinese brand GH4169, and has better tensile strength and room temperature tensile plasticity than the cast Laves eutectic high entropy alloy.
[0017] In a preferred embodiment, M is one or more of the elements Ru, Re, B, etc.
[0018] The present invention provides a high entropy alloy with excellent creep performance, comprising the following steps:
[0019] Step 1
[0020] The raw materials are prepared according to the composition design, and then smelted and suction cast to obtain the cast product;
[0021] Step 2
[0022] The obtained cast product is subjected to homogenization treatment at a temperature of 1200-1300° C., preferably 1240-1280° C., more preferably 1240-1260° C., and the temperature is kept for 20-32 hours, preferably 24 hours;
[0023] Step 3
[0024] The homogenized high entropy alloy ingot is placed in a heating furnace at 1000-1100° C. for 25-60 minutes, preferably 25-35 minutes, and more preferably 30 minutes, and then rolled to a rolling deformation of 35%-90%, preferably 40-80%, and more preferably 60%-75% to obtain a hot-deformed high entropy alloy;
[0025] Step 4
[0026] The hot-deformed high-entropy alloy is placed in a heating furnace at 1100-1250°C, preferably 1150-1200°C, and further preferably 1180-1200°C, and kept warm for 20-32 hours, preferably 24 hours, and then quenched in water to obtain a high-entropy alloy with uniform distribution of spheroidized Laves phase; and then placed in a heat treatment furnace at 750°C-950°C, preferably 800-900°C, and kept warm for 16-48 hours, preferably 24 hours, and then quenched in water to obtain a high-entropy alloy material with nano-scale L12 coherent phase dispersion strengthening.
[0027] The present invention discloses a high entropy alloy with excellent creep performance and a preparation method thereof, wherein the impurity content in the raw material is less than 0.1%. The present invention has no particularly strict requirements on the morphology of the raw material, which can be granular or in other morphologies.
[0028] When used in industry, the raw materials are melted multiple times (3-5 times) in an arc melting furnace with an argon protective atmosphere where titanium absorbs oxygen according to the designed high entropy alloy composition ratio to obtain a master alloy ingot; then the master alloy ingot is remelted in the argon protective atmosphere, and the molten master alloy is cast into a water-cooled copper mold using the suction casting device of the arc furnace to obtain an initial cast high entropy alloy ingot.
[0029] In a preferred solution, the homogenization treatment is followed by water quenching to room temperature, and the water quenching treatment can retain the high-temperature organizational structure.
[0030] In the present invention, micro segregation can be eliminated by homogenizing under the above conditions, so that Laves spheroidization is sufficient and continuous distribution is reduced, thereby reducing crack propagation along the continuous distribution Laves and ensuring mechanical properties.
[0031] In a preferred solution, the heat deformation treatment is followed by water quenching to room temperature, and the water quenching treatment can retain the high-temperature organizational structure.
[0032] The inventors found that the continuously distributed Laves reinforcement phase inside the alloy was broken up by thermal deformation treatment, thereby inhibiting crack propagation along the continuously distributed Laves phase.
[0033] The inventors found that after step 1) heat treatment, the volume fraction of the spheroidized Laves phase did not change much, but the distribution became more uniform and dispersed, while after step 2), a high-density, nanoscale L12 coherent dispersion strengthening phase precipitated in the FCC matrix soft phase of the high entropy alloy material.
[0034] The process parameters of the hot rolling deformation of the present invention have a significant impact on the microstructure of the final material. If the hot rolling deformation is too small, the Laves uniform dispersion distribution effect is not obvious, while if the hot rolling deformation is too large, cracks may be generated and the mechanical properties may be reduced.
[0035] The present invention also provides a high entropy alloy material with excellent creep performance prepared by the above preparation method.
[0036] In a preferred embodiment, the high entropy alloy material with excellent creep performance has a soft (FCC+L12) and hard (Laves) dual-phase structure that synergistically controls the high-temperature creep performance and room-temperature tensile performance of the material.
[0037] The preferred solution is that the obtained nano-scale L12 coherent phase dispersion strengthened high entropy alloy material is a Laves strengthened face-centered cubic high entropy alloy material, which has a life of up to 1245h under 750℃ / 350MPa creep conditions, far exceeding the Chinese high-temperature alloy with the grade GH4169 (greater than or equal to 1000h); the room temperature tensile strength is as high as 1.5GPa, and the elongation after fracture is 5~10%, which can be optimized to 9~10%. Compared with the traditional cast Laves eutectic high entropy alloy, the Laves strengthened face-centered cubic high entropy alloy after thermal deformation has higher strength and significantly improved its plasticity, and has excellent high-temperature creep performance.
[0038] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and equivalent substitutions can be made without departing from the principle of the present invention. The technical solutions obtained by these improvements and equivalent substitutions should also fall within the scope of protection of the present invention.
[0039] Advantages of the present invention:
[0040] 1. The face-centered cubic high entropy alloy synergistically strengthened by the Laves hard-brittle phase and the L12 dispersed nano-precipitate phase provided by the present invention has excellent high-temperature creep performance and room-temperature tensile performance. Under the creep conditions of 750°C / 300MPa, the service life is far longer than that of the high-temperature alloy with the Chinese brand GH4169, and it has room-temperature tensile plasticity and can be processed.
[0041] 2. The face-centered cubic high entropy alloys synergistically strengthened by a series of Laves hard-brittle phases and L12 dispersed nano-precipitates provided by the present invention have a large composition range and a wide range of preparation conditions. The size, volume fraction and distribution of the Laves phase and the L12 nano-precipitates can be adjusted by adjusting the alloy composition and the subsequent thermal deformation and heat treatment processes, thereby achieving regulation of the mechanical properties of the alloy.
[0042] 3. The high entropy alloy with excellent creep performance and the preparation method thereof provided by the present invention are prepared from common non-toxic metal raw materials, with simple production process and short process time, and thus have advantages in safety and economy in engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Fe obtained in Example 1 of the present invention and Comparative Example 1 18.95 Co 25 Cr 18 Ni 26 Ta6Al6B 0.05 Physical picture of alloy ingot prepared by vacuum arc melting of high entropy alloy and corresponding microstructure SEM picture;
[0044] Figure 2 Fe obtained in Example 1 of the present invention 18.95 Co 25 Cr 18 Ni 26 Ta6Al6B 0.05 Scanning electron micrographs of high entropy alloys, showing the macrostructures of the solid solution state, hot rolling + resolidification aging state, and the macrostructures after aging at 800℃ and 900℃;
[0045] Figure 3 The hot-rolled and re-solution-aged Fe 18.95 Co 25 Cr 18 Ni 26 Ta6Al6B 0.05 Transmission electron micrographs of high entropy alloys, and selected area electron diffraction spots of Laves phase and L12 phase;
[0046] Figure 4 High-angle annular dark field scanning transmission image and corresponding energy spectrum of the hot-rolled + re-solution-aged state sample obtained in Example 1 of the present invention.
[0047] Figure 5 Comparison of room temperature tensile property curves of the alloys of Example 1 of the present invention and Comparative Example 1.
[0048] Figure 6 Comparison of high temperature creep performance curves of the alloys of Example 1 of the present invention and Comparative Example 2 under the conditions of 750°C / 350MPa. DETAILED DESCRIPTION
[0049] The following examples are provided in conjunction with the method of the present invention:
[0050] The present invention is described in detail below through specific embodiments and drawings. This embodiment is implemented on the premise of the following technical solution of the present invention, and a detailed implementation method and specific operation process are given.
[0051] The face-centered cubic high entropy alloy used in the following examples has the following composition: Fe a Co b Cr c Ni d Ta p Al q M n (the content of each element is the atomic molar ratio), where 10≤ a ≤20, 20≤ b ≤25, 10≤ c ≤20, 25≤ d ≤35, 5≤ p≤10, 0≤ q ≤8, 0≤ n ≤5, and a+b+c+d+p+q+n=100;
[0052] Embodiment 1:
[0053] Fe 18.95 Co 25 Cr 18 Ni 26 Ta6Al6B 0.05 Face-centered cubic high entropy alloy and preparation method thereof, the preparation process is as follows:
[0054] S1: face-centered cubic high-entropy alloy ingots were prepared by vacuum arc melting technology;
[0055] S2: The face-centered cubic high entropy alloy ingot obtained in step S1 is homogenized at 1250° C. for 24 hours and cut into 4 mm thick alloy plates by wire cutting;
[0056] S3: The face-centered cubic high entropy alloy plate obtained in step S2 is subjected to a hot deformation treatment with a rolling reduction of 70% after being kept at 1100° C. for 30 minutes;
[0057] S4: subjecting the hot-deformed face-centered cubic high entropy alloy obtained in step S3 to a heat treatment process, wherein the alloy is kept at 1250° C. for 24 hours and water quenched; the alloy is kept at 800° C. for 24 hours and water quenched to obtain a face-centered cubic high entropy alloy synergistically strengthened by Laves hard-brittle phase and L12 dispersed nano-precipitate phase, so that the alloy has good processing properties;
[0058] The face-centered cubic high entropy alloy synergistically strengthened by the Laves hard-brittle phase and the L12 dispersed nano-precipitate phase obtained in the above steps was characterized for its microstructure and tested for high-temperature creep properties and room-temperature tensile properties.
[0059] The high temperature creep test of the alloy was carried out in the RDJ-30 mechanical creep test machine. The test temperature range is 750-900℃, and the loading stress range is 170-400MPa. The specimen is a standardized plate-shaped specimen with a test section length of 10mm and a width of 3mm. The product alloy obtained after heat treatment has a high temperature creep life of 1245h at 750℃ / 350MPa.
[0060] The room temperature uniaxial tensile test was carried out on an Instron mechanical testing machine at a strain rate of 10 -3 s -1 The specimen is an I-shaped specimen with a test section length of 3 mm and a width of 1.5 mm. During the test, an AVE 2-model 2663-901 Instron video extensometer was used to test the length change of the specimen gauge length. The room temperature tensile strength of the product alloy obtained after heat treatment was 1529 MPa, and the elongation at break was 9.5%.
[0061] Embodiment 2:
[0062] The specific composition of the alloy is Fe 19Co 25 Cr 18 Ni 26 Ta6Al5Ru 1.5 , other preparation conditions are the same as those in Example 1.
[0063] Finally, the material's 750℃ / 300MPa high-temperature creep life is 47h; the room-temperature tensile strength is 1476MPa, and the elongation at break is 4.5%.
[0064] Embodiment 3:
[0065] Other conditions are the same as those in Example 1, except that the hot deformation reduction is 40%.
[0066] Finally, the room temperature tensile mechanical properties of the material were obtained as follows: tensile strength was 1463MPa and elongation at break was 4.4%.
[0067] Comparative Example 1:
[0068] Cast Fe without hot deformation and heat treatment process 18.95 Co 25 Cr 18 Ni 26 Ta6Al6B 0.05 The room temperature tensile mechanical properties of the face-centered cubic high entropy alloy are: tensile strength is 1149MPa and elongation at break is 2.6%.
[0069] Comparative Example 2:
[0070] Calvin M. Stewart studied the high temperature creep properties of IN718 alloy (Chinese grade GH4169) at 750℃ / 350MPa, and the tested creep life was 42.7h.
Claims
1. A high entropy alloy with excellent creep properties, characterized in that: The alloy composition is expressed in atomic mole percentage, and the expression is: Fe a Co b Cr c Ni d Ta p Al q M n , wherein M is one or more of rare earth elements, B, C, Si, and P; wherein 10≤a≤20, 20≤b≤25, 10≤c≤20, 25≤d≤35, 5≤p≤10, 0≤q≤8, 0≤n≤5, and a+b+c+d+p+q+n=100.
2. A high entropy alloy with excellent creep properties according to claim 1, characterized in that: The alloy composition is expressed in atomic mole percentage, and the expression is: Fe a Co b Cr c Ni d Ta p Al q M n , M is one or more of rare earth elements, B, C, Si, and P; wherein 16≤a≤20, 23≤b≤25, 16≤c≤20, 25≤d≤28, 5≤p≤8, 5≤q≤8, 0≤n≤1 and a+b+c+d+p+q+n=100, and the rare earth element is Ru and / or Re.
3. A high entropy alloy with excellent creep properties according to claim 2, characterized in that: The alloy composition is expressed in atomic mole percentage, and the expression is: Fe a Co b Cr c Ni d Ta p Al q M n , M is one or more of rare earth elements, B, C, Si, and P; wherein 18≤a≤19, 24.5≤b≤25, 17.5≤c≤18.5, 25.5≤d≤26.5, 5.5≤p≤6.5, 5.5≤q≤6.5, 0.02≤n≤0.1 and a+b+c+d+p+q+n=100, and the rare earth element is Ru and / or Re.
4. A high entropy alloy with excellent creep properties according to claim 1, characterized in that: It contains a soft matrix and a hard phase, wherein the soft matrix includes at least one of the FCC phase and the L12 phase, preferably a composite of the FCC phase and the L12 phase, and the hard phase includes at least one of the Laves phase, the B2 phase, the σ phase, and the η phase, preferably the Laves phase.
5. The high entropy alloy with excellent creep performance according to claim 1, characterized in that: The hard phase is a reinforcing phase; the Laves phase is preferably a C14 type Laves phase.
6. A method for preparing a high entropy alloy having excellent creep properties as claimed in any one of claims 1 to 5, characterized in that The steps include: Step 1 The raw materials are prepared according to the composition design, and then smelted and suction cast to obtain the cast product; Step 2 The obtained cast product is subjected to homogenization treatment at a temperature of 1200-1300° C., preferably 1240-1280° C., more preferably 1240-1260° C., and the temperature is kept for 20-32 hours, preferably 24 hours; Step 3 The homogenized high entropy alloy ingot is placed in a heating furnace at 1000-1100° C. for 25-60 minutes, preferably 25-35 minutes, and more preferably 30 minutes, and then rolled to a rolling deformation of 35%-90%, preferably 40-80%, and more preferably 60%-75% to obtain a hot-deformed high entropy alloy; Step 4 The hot-deformed high-entropy alloy is placed in a heating furnace at 1100-1250°C, preferably 1150-1200°C, and further preferably 1180-1200°C, and kept warm for 20-32 hours, preferably 24 hours, and then quenched in water to obtain a high-entropy alloy with uniform distribution of spheroidized Laves phase; and then placed in a heat treatment furnace at 750°C-950°C, preferably 800-900°C, and kept warm for 16-48 hours, preferably 24 hours, and then quenched in water to obtain a high-entropy alloy material with nano-scale L12 coherent phase dispersion strengthening.
7. The method for preparing a high entropy alloy with excellent creep performance according to claim 6, characterized in that: The impurity content in the raw materials is less than 0.1%.
8. The method for preparing a high entropy alloy with excellent creep performance according to claim 6, characterized in that: According to the designed high entropy alloy composition ratio, each raw material is melted 3 to 5 times in an arc melting furnace with an argon protective atmosphere where titanium absorbs oxygen to obtain a master alloy ingot; then the master alloy ingot is remelted in the argon protective atmosphere, and the molten master alloy is cast into a water-cooled copper mold using the suction casting device of the arc furnace to obtain an initial cast high entropy alloy ingot.
9. The method for preparing a high entropy alloy with excellent creep performance according to claim 6, characterized in that: The obtained nanoscale L12 coherent phase dispersion strengthened high entropy alloy material is a Laves strengthened face-centered cubic high entropy alloy material, which has a life of greater than or equal to 1000h under 750℃ / 350MPa creep conditions; the room temperature tensile strength is as high as 1.5GPa, and the elongation at break is 5~10%, which can be optimized to 9~10%.
Citation Information
Patent Citations
High-entropy alloy and preparation method thereof
CN108642362A
Eutectic high-entropy alloy and preparation method thereof
CN109706363A
Ti-Ta-Nb-Zr-Mo biomedical high-entropy alloy
CN115109979A
High-temperature oxidation-resistant eutectic high-entropy alloy material and preparation method thereof
CN118241097A
High-strength multi-heterostructure eutectic high-entropy alloy and preparation method thereof
CN118639083A
Cited By
Directional solidification preparation method of high-strength and high-toughness eutectic high-entropy alloy
CN121320811A